2012
DOI: 10.1007/s10792-012-9568-7
|View full text |Cite
|
Sign up to set email alerts
|

Is axial length a risk factor for idiopathic macular hole formation?

Abstract: Current theories for macular hole formation implicate antero-posterior and tractional forces at the vitreofoveal interface. It is thought that localized perifoveal defects enlarge from centrifugal forces acting about the axis of ocular rotation. If this is true, eyes with longer axial lengths should have an increased incidence of macular holes. The aim of this study was to determine if axial length is a risk factor for macular hole development. The study group comprised 40 patients with refractive errors from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For example, what causes the traction by the posterior hyaloid on the retinal surface, and how does the fragility and stiffness of the retina affect the formation of a MH. Because a MH has a higher incidence in eyes with longer axial lengths (myopia) and in older individuals, especially women, we can reasonably assume that the structure of the eye and changes in the structure with increasing age could be involved in the pathogenesis of MHs [ 9 11 ]. For example, it has been shown that the retinal thickness decreases with increasing age which should make the retinas of older individuals more susceptible to MH formation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, what causes the traction by the posterior hyaloid on the retinal surface, and how does the fragility and stiffness of the retina affect the formation of a MH. Because a MH has a higher incidence in eyes with longer axial lengths (myopia) and in older individuals, especially women, we can reasonably assume that the structure of the eye and changes in the structure with increasing age could be involved in the pathogenesis of MHs [ 9 11 ]. For example, it has been shown that the retinal thickness decreases with increasing age which should make the retinas of older individuals more susceptible to MH formation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that the retinal thickness decreases with increasing age which should make the retinas of older individuals more susceptible to MH formation [ 11 ]. In addition, the incidence of MHs is higher in highly myopic eyes than in emmetropic eyes [ 9 ]. This is most likely because myopic eyes have longer axial lengths and thinner retinas.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma, tractional forces at the vitreofoveal interface, and aging have all been implicated in development of macular hole. Recently, eyes with increased axial length and thus greater dynamic forces at the macula have also been associated with increased macular hole formation 6. We present a series of three patients who developed an idiopathic macular hole after DLP.…”
Section: Discussionmentioning
confidence: 96%
“…Macular hole (MH) is an idiopathic condition that in most cases is related to posterior vitreous detachment (PVD) and is mainly seen in the elderly. The minority of cases are observed in younger patients with a history of blunt ocular trauma as well as in myopic patients after laser assisted in situ keratomileusis (LASIK) surgery [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%